Kawasaki disease fact check: Myths, misconceptions and mysteries. (8th August 2020) - Butters, Coen; Curtis, Nigel; Burgner, David P
Abstract : Kawasaki disease (KD) is an important cause of childhood vasculitis and a common cause of acquired heart disease in children world‐wide. The emergence of Paediatric Multisystem Inflammatory Syndrome‐Temporally Associated with SARS‐CoV‐2, a KD‐like hyperinflammatory syndrome and the recent death of Dr Tomisaku Kawasaki make this a timely review. Although KD was described by Dr Kawasaki over 50 years ago, there is still no specific diagnostic test and the aetiology remains elusive. This article summarises the latest evidence, highlights important myths and misconceptions and discusses some of the mysteries that surround this disease.